Reliability and Validity of the Persian Version Emotional Self-efficacy Scale for Young Adolescents - Zahra Mohammadi; Zohreh Meshkati (Gonabad University of Medical Sciences, 2021)
Background: The present research aimed at determining the reliability and validity of the Persian version of the Emotional Self-Efficiency Scale (ESES) for adolescents of Isfahan city. This study was conducted using a developmental research method. The statistical population consisted of all the first-grade high school students of Isfahan city in 2018 (n=59396). Methods: A total number of 280 students (160 girls and 120 boys, mean±SD age of 12.98±1.14) were selected using a stratified random sampling method, and completed ESES for adolescents (2015), as well as Self-Efficacy Questionnaire for Children (2001). Results: An Exploratory Factor Analysis (EFA) revealed the four-factor structure of ESES. A Confirmatory Factor Analysis (CFA) also confirmed the fit of the four-factor structure of the scale. The results of the within-group correlation coefficient were obtained to investigate the acceptable test-retest reliability. The results of the correlation between the above-mentioned scale and SEQ-C instrument was also significant (P<0.05). Moreover, ESES and its dimensions had proper reliability over time. The reliability obtained by Cronbach's alpha for all four dimensions of the questionnaire, given the number of items, was higher than 0.5 for each dimension and higher than 0.7 for the whole scale, which was acceptable. Conclusion: These findings indicate the acceptable validity and reliability of ESES for Isfahan's adolescents, and its validity and reliability should be investigated in broader research on Iranian children and adolescents.